2013
DOI: 10.1002/jnr.23280
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor 4 activation increases the expression of calcitonin gene‐related peptide mRNA and protein in dorsal root ganglion neurons

Abstract: Accumulating evidence demonstrates that nociceptor activation evokes a rapid change in mRNA and protein levels of calcitonin gene-related peptide (CGRP) in dorsal root ganglion (DRG) neurons. Although the colocalization of CGRP and protease-activated receptor-4 (PAR4), a potent modulator of pain processing and inflammation, was detected in DRG neurons, the role of PAR4 activation in the expression of CGRP has not been investigated. In the present study, the expression of CGRP and activation (phosphorylation) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Accumulating evidence demonstrates that nociceptor activation and inflammation evoke a rapid change in the levels of CGRP mRNA and protein in DRG neurons, [26][27][28] and CGRP expression in these neurons contributes to the regulation of neurogenic inflammation and pain. [29][30][31][32] In a previous study, the PAR4 agonist did not induce a calcium signal in DRG neurons; it reduced the calcium signal of DRG neurons in response to KCl, 16 suggesting that PAR4 activation could inhibit the nociceptive signal in DRG neurons. Furthermore, in an in vivo experiment, the PAR4 agonist was able to increase the nociceptive threshold to thermal and mechanical stimuli, and to reduce thermal and mechanical inflammatory hyperalgesia and allodynia.…”
Section: Expression Of Par4 In Sensory Neuronsmentioning
confidence: 87%
See 3 more Smart Citations
“…Accumulating evidence demonstrates that nociceptor activation and inflammation evoke a rapid change in the levels of CGRP mRNA and protein in DRG neurons, [26][27][28] and CGRP expression in these neurons contributes to the regulation of neurogenic inflammation and pain. [29][30][31][32] In a previous study, the PAR4 agonist did not induce a calcium signal in DRG neurons; it reduced the calcium signal of DRG neurons in response to KCl, 16 suggesting that PAR4 activation could inhibit the nociceptive signal in DRG neurons. Furthermore, in an in vivo experiment, the PAR4 agonist was able to increase the nociceptive threshold to thermal and mechanical stimuli, and to reduce thermal and mechanical inflammatory hyperalgesia and allodynia.…”
Section: Expression Of Par4 In Sensory Neuronsmentioning
confidence: 87%
“…The percentages of total DRG neurons expressing both CGRP and PAR4 or p-ERK1/2 also increased significantly at 2h after PAR4-AP treatment. 32,103,104 Moreover, previous studies have reported that noxious stimulation immediately increases p-ERK1/2 expression in the cytoplasm and nucleus of DRG neurons, all of which are features of small-and medium-sized nociceptive neuronal cells. 16,33,105 Furthermore, membrane depolarization and calcium influx evoked by noxious stimulation lead to ERK1/2 activation, 106 which triggers CREB-induced transcription and upregulation of CGRP mRNA levels in DRG neurons.…”
Section: Par4 Activation Increases the Release Of Cgrpmentioning
confidence: 95%
See 2 more Smart Citations
“…PAR4-AP evokes the overexpression of CGRP via activation of the ERK1/2 signaling pathway, and PAR4 activation notably enhances the levels of CGRP messenger RNA (mRNA) and protein in DRG neurons in the presence of AYPGKF-NH2 both in vivo and in vitro [72]. Remarkably, this overexpression is significantly attenuated after inhibiting ERK1/2 phosphorylation.…”
Section: Erk/mapkmentioning
confidence: 97%